Nickel Glyoximate Based Metal–Covalent Organic Frameworks for Efficient Photocatalytic Hydrogen Evolution. (8th June 2022) - Sun, Lishan; Lu, Meng; Yang, Zongfan; Yu, Zhenyi; Su, Xi; Lan, Ya‐Qian; Chen, Long
Abstract: Metal–covalent organic frameworks (MCOFs) have been recently received wide attention owing to the homogeneous distribution of active metal centers that are beneficial for enhancing the application potentials. However, metal complex based functional building blocks for MCOFs synthesis are limited. Herein, two new MCOFs (Ni‐Py‐COF and Ni‐Bn‐COF) were constructed via a novel nickel glyoximate based building block. Splendid photocatalytic activity on hydrogen evolution from water and great long‐term recyclability were achieved using these nickel glyoximate based MCOFs as photocatalysts. Excitingly, even without the addition of Pt co‐catalyst, the hydrogen evolution rates (HER) of Ni‐Py‐COF reached up to 626 μmol g −1  h −1, which is better than many porous organic polymers. This work not only expands the type of building units for MCOFs, but also provides meaningful insights for developing stable, efficient and earth‐abundant photocatalysts toward H2 generation. Abstract : To enrich the diversity of metal–covalent organic frameworks (MCOFs), two novel nickel glyoximate based MCOFs have been developed. Notably, favourable photocatalytic hydrogen evolution activities were achieved thanks to the uniformly and densely distributed Ni glyoximate functional cores on the Ni‐glyoximate‐COF skeletons.